Outspoken Objects and Unspoken Myths: The Semiotics of Object‐Mediated Communication. Issue 3 (6th November 2019) - Peña‐Alves, Stephanie
Abstract : This interactionist study draws on the semiotics of Peirce and Barthes to theorize object‐mediated communication, a nonverbal interpersonal technique in which individuals signal new information by using and orienting themselves to symbolically endowed material objects. Examining the case of door‐mediated communication, it proposes that objects lie symbolically dormant until their deeper collective significance is activated through their use in interaction. The article expands the scope of interactionist inquiry on human–nonhuman relations by moving beyond the dominant scholarly focus on identity. The semiotic approach foregrounds a distinct human–object phenomenon, a novel category of nonverbal communication, and important meaning‐making dynamics.